High-ionic-conductivity flexible polymer solid electrolyte as well as preparation method and application thereof
By using a specific polymer monomer skeleton, plasticizer and photoinitiator in the polymer solid electrolyte, combined with ultrasonic mixing and ultraviolet light curing processes, the problem of the polymer solid electrolyte being difficult to achieve both high ionic conductivity and high mechanical strength is solved. problem, achieving a balance of efficient electrochemical performance and mechanical properties.
Patent Information
- Application Number
- CN202411455484.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
Existing polymer solid electrolytes are difficult to take into account high ionic conductivity and high mechanical strength, resulting in poor performance of batteries in high magnification and flexible applications.
Ethoxylated trimethylolpropane triacrylate is used as the polymer monomer skeleton, combined with succinonitrile as the plasticizer and 2,2-dimethoxy-2-phenylacetophenone as the photoinitiator. The flexible polymer solid electrolyte was prepared by ultraviolet light curing after ultrasonic mixing.
The balance of high ion conductivity and good mechanical properties, so that the room temperature ion conductivity of the polymer solid electrolyte can exceed 2 × 10 –3s/cm, which is suitable for fast charging requirements and perform excellent performance in curve and electrochemical stability. Essence
Smart Images

Figure CN119340468A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a high-ionic-conductivity flexible polymer solid electrolyte and a preparation method and application thereof. Background Art
[0002] The large-scale development of lithium-ion batteries is restricted by the scarcity and uneven distribution of lithium resources. With the increasing severity of the global energy crisis and environmental problems, the development of efficient, safe and environmentally friendly energy storage devices to replace traditional lithium-ion batteries has become a research hotspot. Sodium-based batteries have attracted attention due to their abundant resources and similar working principles to lithium-based batteries. However, the currently commonly used sodium-based batteries use liquid electrolytes, which have risks such as electrolyte volatilization, combustion, and leakage.
[0003] Introducing solid electrolytes to replace liquid electrolytes and separators is considered to be one of the most effective strategies to solve the above problems. Solid-state batteries use solid electrolytes instead of liquid electrolytes, which greatly improves the safety of the battery and is compatible with high-energy-density electrode materials (such as high-nickel materials, metal negative electrodes, etc.), thereby further improving the energy density of the battery.
[0004] Polymer solid electrolytes have become one of the research hotspots due to their advantages such as good flexibility, easy processing and forming, and the ability to form thin films. Existing polymer solid electrolytes are usually composed of components such as polymer matrix, plasticizer and lithium salt. However, existing polymer solid electrolytes still have problems such as low ionic conductivity, large interface impedance and poor electrochemical stability, making it difficult to achieve the operation of all-solid-state batteries.
[0005] In previous studies, UV curing has attracted widespread attention because of its simplicity and high efficiency. CN116864784A discloses a method for improving the ionic conductivity of polymer-based solid electrolytes by designing a polymer matrix, adding ceramic fillers, and introducing additives. However, the addition of ceramic fillers will increase the cost of the electrolyte and make it difficult to disperse the components, resulting in low preparation efficiency and high cost. In addition to adding inorganic fillers, the intermolecular interactions are adjusted to develop polymer electrolytes with acceptable ionic conductivity and high mechanical strength. However, polymer-based electrolytes with high ionic conductivity usually compromise on mechanical strength, and most studies on optimizing the performance of polymer-based electrolytes attempt to strike a balance between mechanical strength and ionic conductivity.
[0006] Therefore, there is an urgent need to develop a polymer solid electrolyte that has both high ionic conductivity and high mechanical strength. Summary of the invention
[0007] The purpose of the present invention is to provide a high ionic conductivity flexible polymer solid electrolyte and a preparation method and application thereof, so as to solve the problem that the existing polymer solid electrolyte is difficult to achieve both high ionic conductivity and high mechanical strength.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solution: a high ionic conductivity flexible polymer solid electrolyte, characterized in that it is prepared from the following raw materials in parts by weight:
[0009]
[0010] A further technical solution is that the polymer monomer skeleton is ethoxylated trimethylolpropane triacrylate.
[0011] A further technical solution is that the plasticizer is succinonitrile.
[0012] A further technical solution is that the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone.
[0013] A further technical solution is that the sodium salt is sodium bis(fluorosulfonyl)imide.
[0014] The present invention also discloses a method for preparing a high ionic conductivity flexible polymer solid electrolyte, which is characterized by comprising the following steps:
[0015] 1) Ultrasonic mixing of polymer monomer skeleton, plasticizer, photoinitiator and sodium salt to obtain flexible polymer solid electrolyte precursor slurry;
[0016] 2) pouring the precursor slurry described in step 1) onto an insulating plate, and adjusting the thickness with a scraper to obtain a flexible polymer solid electrolyte precursor;
[0017] 3) The precursor obtained in step 2) is cured by ultraviolet light to obtain a polymer solid electrolyte.
[0018] A further technical solution is that the conditions for ultrasonic mixing are: ultrasonic frequency is 60-80 Hz; mixing time is 20-30 min; mixing temperature is 30-50°C.
[0019] A further technical solution is to adjust the thickness to 80-120 μm.
[0020] A further technical solution is that the ultraviolet light irradiation conditions are: the light wavelength is 356nm; the irradiation time is 15S / time; the number of irradiations is 3 times.
[0021] A further technical solution is to assemble the polymer solid electrolyte with commercial positive and negative electrodes to obtain an all-solid-state battery.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. A three-dimensional ion transmission channel is constructed through intermolecular interactions, which shortens the ion transmission distance, increases the ion conductivity, and makes high-rate solid-state batteries possible.
[0024] 2. The present invention is solvent-free and easy to operate, and can be applied to acrylic polymer solid electrolyte systems. The flexible polymer solid electrolyte prepared by the present invention has high ionic conductivity, good mechanical properties, and good positive electrode-electrolyte contact interface. This simple and fast preparation method greatly gets rid of the dependence on solvents, improves ionic conductivity, and is conducive to simplifying the battery assembly process.
[0025] 3. The flexible polymer solid electrolyte provided by the present invention has better performance, and the room temperature ionic conductivity can exceed 2×10 – 3 S / cm, which can meet the requirements of modern energy fast charging; it can be bent 180° without breakage, and its application in flexible electronic products can improve user experience; the electrochemical stability window is as high as 4.8V, which can be adapted to high specific capacity electrodes to obtain higher energy density batteries.
[0026] 4. The flexible solid electrolyte provided by the present invention has good interface contact with the electrode, and the all-solid-state battery can be stably cycled at room temperature. At a current density of 0.1C, the all-solid-state battery with sodium metal as the negative electrode and sodium vanadium phosphate as the positive electrode can provide a capacity of 95mAh / g. After 100 cycles, the capacity retention rate is as high as 95.49%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an XRD curve diagram of the polymer solid electrolyte in an embodiment of the present invention.
[0028] Figure 2 This is a graph of the cycle performance of the all-solid-state battery in Example 5 of the present invention.
[0029] Figure 3 Graph showing the capacity-voltage curves of the all-solid-state battery in Example 5 of the present invention at the 1st, 50th and 100th cycles at a current density of 0.1C at room temperature.
[0030] Figure 4 This is a graph showing the limiting current density of the sodium all-solid-state symmetrical battery in Example 5 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0032] Example 1
[0033] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% polyvinylidene fluoride (PVDF), 10% conductive carbon black (SuperP) and N-methylpyrrolidone (NMP) are mixed and stirred evenly to obtain positive electrode slurry, and then the slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0034] Preparation of polymer solid electrolyte:
[0035] Step (1): weigh 2.8 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 1.2 g of succinonitrile and 0.056 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.5 g of sodium salt of sodium bis(fluorosulfonyl)imide NaFSI;
[0036] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 30° C. for 30 min to obtain a flexible polymer solid electrolyte precursor slurry in which all substances are uniformly mixed;
[0037] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to 120 μm with a scraper;
[0038] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0039] The negative electrode is a metallic sodium sheet.
[0040] Preparation of all-solid-state batteries:
[0041] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0042] Example 2
[0043] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0044] Preparation of polymer solid electrolyte:
[0045] Step (1): weigh 2.4 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 1.6 g of succinonitrile and 0.048 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.5 g of sodium salt of sodium bis(fluorosulfonyl)imide NaFSI;
[0046] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0047] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to 100 μm with a scraper;
[0048] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0049] The negative electrode is a metallic sodium sheet.
[0050] Preparation of all-solid-state batteries:
[0051] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0052] Example 3
[0053] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0054] Preparation of polymer solid electrolyte:
[0055] Step (1): weigh 2 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 2 g of succinonitrile and 0.04 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.5 g of sodium salt NaFSI;
[0056] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 45° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0057] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to 120 μm with a scraper;
[0058] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0059] The negative electrode is a metallic sodium sheet.
[0060] Preparation of all-solid-state batteries:
[0061] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0062] Example 4
[0063] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0064] Preparation of polymer solid electrolyte:
[0065] Step (1): weigh 1.6 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 2.4 g of succinonitrile and 0.032 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.5 g of sodium salt NaFSI;
[0066] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0067] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to less than 100 μm with a scraper;
[0068] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0069] The negative electrode is a metallic sodium sheet.
[0070] Preparation of all-solid-state batteries:
[0071] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0072] Example 5
[0073] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0074] Preparation of polymer solid electrolyte:
[0075] Step (1): weigh 1.2 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 2.8 g of succinonitrile and 0.024 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.5 g of sodium salt NaFSI;
[0076] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0077] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to 100 μm with a scraper;
[0078] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0079] The negative electrode is a metallic sodium sheet.
[0080] Preparation of all-solid-state batteries:
[0081] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0082] Example 6
[0083] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0084] Preparation of polymer solid electrolyte:
[0085] Step (1): weigh 2 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 2 g of succinonitrile and 0.04 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.667 g of sodium salt NaFSI;
[0086] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0087] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to 100 μm with a scraper;
[0088] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0089] The negative electrode is a metallic sodium sheet.
[0090] Preparation of all-solid-state batteries:
[0091] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0092] Example 7
[0093] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0094] Preparation of polymer solid electrolyte:
[0095] Step (1): weigh 2 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 2 g of succinonitrile and 0.04 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 1.0 g of sodium salt NaFSI;
[0096] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0097] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to less than 100 μm with a scraper;
[0098] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0099] The negative electrode is a metallic sodium sheet.
[0100] Preparation of all-solid-state batteries:
[0101] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0102] Comparative Example 1
[0103] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0104] Preparation of polymer solid electrolyte:
[0105] Step (1): weigh 4 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 0.08 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.5 g of sodium salt NaFSI;
[0106] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0107] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to less than 100 μm with a scraper;
[0108] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0109] The negative electrode is a metallic sodium sheet.
[0110] Preparation of all-solid-state batteries:
[0111] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0112] Comparative Example 2
[0113] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0114] Preparation of polymer solid electrolyte:
[0115] Step (1): weigh 4 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 0.08 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 0.667 g of sodium salt NaFSI;
[0116] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0117] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to 100 μm with a scraper;
[0118] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0119] The negative electrode is a metallic sodium sheet.
[0120] Preparation of all-solid-state batteries:
[0121] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0122] Comparative Example 3
[0123] Preparation of positive electrode sheet: 80% sodium vanadium phosphate, 10% PVDF, 10% Super P and NMP were mixed and stirred evenly to obtain positive electrode slurry, and then the slurry was evenly coated on the surface of the positive electrode collector aluminum foil, and dried at 60°C for 24h to obtain the positive electrode sheet.
[0124] Preparation of polymer solid electrolyte:
[0125] Step (1): weigh 4 g of ethoxylated trimethylolpropane triacrylate (Mw=550), 0.08 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, and 1.0 g of sodium salt NaFSI;
[0126] Step (2): adding the substances weighed in step (1) into a brown glass bottle and mixing them by ultrasonication at a frequency of 75 Hz and a temperature of 40° C. for 30 min to obtain a liquid electrolyte slurry in which all substances are uniformly mixed;
[0127] Step (3): pour the slurry obtained in step (2) onto the insulating board and adjust the thickness to 100 μm with a scraper;
[0128] Step (4): The solid electrolyte precursor of step (3) is cured by ultraviolet light with a wavelength of 356 nm, and the light is irradiated three times, each time for 15 seconds.
[0129] The negative electrode is a metallic sodium sheet.
[0130] Preparation of all-solid-state batteries:
[0131] The all-solid-state battery can be obtained by assembling the above-mentioned positive electrode, electrolyte and sodium metal.
[0132] Example 8
[0133] Performance comparison and effect evaluation:
[0134] Battery electrochemical impedance test: The assembled stainless steel||stainless steel symmetrical battery was tested by using Solartron electrochemical workstation and Solartron 11260A electrochemical impedance tester from Ametek, UK. The test frequency range is: 1×10 – 6 ~0.1Hz.
[0135] Electrochemical window test: The electrochemical stability window of the composite electrolyte was evaluated by linear sweep voltammetry (LSV) on a stainless steel||CSE||Na cell with a scan rate of 2 mV / s and a scan voltage from 0 to 6 V (VS. Na / Na + ).
[0136] Based on the method of Example 5, the components and comparative example composition, process parameters, and test results are adjusted as shown in Table 1 (ethoxylated trimethylolpropane triacrylate: ETPTA, succinonitrile: SCN, sodium bis(fluorosulfonyl)imide: NaFSI, 2,2-dimethoxy-2-phenylacetophenone: DMPA):
[0137] Table 1. Composition, process parameters, and test results of the examples and comparative examples
[0138]
[0139]
[0140] Examples 1 to 5 are different ETPTA:SCN. As SCN increases, the ionic conductivity increases, and Example 5 reaches 2.89 mS / cm. The increase in SCN will also reduce the mechanical strength of the polymer solid electrolyte. The ratio of the two can be adjusted in combination with actual application scenarios to obtain a suitable polymer solid electrolyte.
[0141] Examples 6 to 7 are polymer solid electrolytes with different salt contents when the amount of ETPTA:SCN is 2 g each. As the salt content increases, the interaction between the polymer and the anion becomes stronger after the salt concentration is saturated, which limits ion migration and reduces the ionic conductivity of the polymer solid electrolyte.
[0142] Comparative Examples 1 to 3 are polymer solid electrolytes with different sodium salt contents without succinonitrile, and the ion conductivities are all relatively low. This is because the polymer solid electrolytes have high crystallinity and small ion transport areas.
[0143] Figure 1 2 are XRD diagrams of the polymer solid electrolytes of Examples 1 to 5. As the amount of succinonitrile increases, the crystallinity of the polymer solid electrolyte decreases. Except for Example 1, the other polymer solid electrolytes are amorphous, which is more conducive to ion transport.
[0144] The present invention realizes the preparation of polymer solid electrolyte by ultraviolet light curing, and the process is green, simple, solvent-free and scalable.
[0145] In order to test the actual application performance of the battery, an all-solid-state battery was assembled using the polymer solid electrolyte of Example 5 and further tested.
[0146] Battery charge and discharge test: Use the Blue Power Battery Test System model CT2001A to place the assembled battery at room temperature for more than 8 hours, and then use the Blue Power Battery Charge and Discharge Tester to test it. For NVP||Na full batteries, the charge and discharge voltage range is 2.5~4V. The test results and analysis are as follows:
[0147] Figure 2This is the all-solid-state battery cycle performance diagram of Example 5. Benefiting from the high ionic conductivity and good flexibility of the polymer solid electrolyte, the room temperature all-solid-state battery achieves normal operation. At a current density of 0.1C, the capacity can reach 90mAh / g. After 100 cycles, the capacity retention rate is as high as 97.6%.
[0148] Figure 3 The capacity-voltage curves of the all-solid-state battery of Example 5 at the 1st, 50th, and 100th cycles at room temperature and 0.1C current density show that the battery has a small polarization, indicating that the battery interface contact is good and the interface impedance is low. The curve does not change significantly during the cycle, indicating that the polymer solid electrolyte has good stability with the electrode.
[0149] Figure 4 This is the limiting current density test curve of the all-solid-state sodium-sodium symmetric battery in Example 5. The sodium-sodium symmetric all-solid-state battery can operate normally at room temperature with a limiting current density of up to 1.2 mA / cm 2 , which can adapt to modern fast charging requirements for energy storage batteries.
[0150] From the above analysis, it can be seen that when comparing the embodiment with the comparative example, the ionic conductivity of the polymer solid electrolyte is greatly improved due to the addition of succinonitrile. Succinonitrile effectively reduces the crystallinity of the polymer solid electrolyte, and there is a larger amorphous region to transmit ions. The room temperature ionic conductivity of the polymer solid electrolyte can reach 2.89mS / cm. Benefiting from the high ionic conductivity and good flexibility of the polymer solid electrolyte, the room temperature all-solid-state battery can operate normally and has good cycle stability. The present invention provides a high-performance polymer solid electrolyte and an effective method for all-solid-state batteries, and the relevant performance reaches the world's advanced level, which has a certain reference significance for realizing the large-scale preparation of all-solid-state batteries.
[0151] Although the present invention is described herein with reference to a number of illustrative embodiments of the present invention, it will be appreciated that those skilled in the art may devise numerous other modifications and implementations that fall within the scope of the present disclosure. More specifically, within the scope of the present disclosure, drawings, and claims, a variety of variations and modifications may be made to the components or layout. In addition to variations and modifications to the components or layout, other uses will be apparent to those skilled in the art.
Claims
1. A high ionic conductivity flexible polymer solid electrolyte, characterized in that: Prepared from the following raw materials:
2. The high ionic conductivity flexible polymer solid electrolyte according to claim 1, characterized in that: The polymer monomer backbone is ethoxylated trimethylolpropane triacrylate.
3. The high ionic conductivity flexible polymer solid electrolyte according to claim 1, characterized in that: The plasticizer is succinonitrile.
4. The high ionic conductivity flexible polymer solid electrolyte according to claim 1, characterized in that: The photoinitiator is 2,2-dimethoxy-2-phenylacetophenone.
5. The high ionic conductivity flexible polymer solid electrolyte according to claim 1, characterized in that: The sodium salt is sodium bis(fluorosulfonyl)imide.
6. The method for preparing a high ionic conductivity flexible polymer solid electrolyte according to any one of claims 1 to 5, characterized in that: The steps include: 1) Ultrasonic mixing of polymer monomer skeleton, plasticizer, photoinitiator and sodium salt to obtain flexible polymer solid electrolyte precursor slurry; 2) pouring the precursor slurry described in step 1) onto an insulating plate, and adjusting the thickness with a scraper to obtain a flexible polymer solid electrolyte precursor; 3) The precursor obtained in step 2) is cured by ultraviolet light to obtain a polymer solid electrolyte.
7. The method for preparing a high ionic conductivity flexible polymer solid electrolyte according to claim 6, characterized in that: The conditions for ultrasonic mixing are: ultrasonic frequency of 60-80 Hz; mixing time of 20-30 min; mixing temperature of 30-50° C.
8. The method for preparing a high ionic conductivity flexible polymer solid electrolyte according to claim 6, characterized in that: The thickness is 80-120 μm.
9. The method for preparing a high ionic conductivity flexible polymer solid electrolyte according to claim 6, characterized in that: The ultraviolet light irradiation conditions are as follows: the wavelength of the light is 356nm; the irradiation time is 15S / time; and the number of irradiations is 3 times.
10. The method for preparing a high ionic conductivity flexible polymer solid electrolyte according to claim 6, characterized in that: The polymer solid electrolyte is assembled with commercial positive and negative electrodes to obtain an all-solid-state battery.
Citation Information
Patent Citations
Positive electrode-electrolyte integrated solid sodium battery and preparation method thereof
CN116864784A